Video streaming performance under wellknown packet scheduling algorithms - Mohd. Ramli, Huda Adibah; Sandrasegaran, Kumbesan; Basukala, Riyaj; Patachaianand, Rachod; Afrin, Toyoba Sohana (Academy & Industry Research Collaboration Center (AIRCC), 2011)
Video streaming is becoming increasingly popular among the wireless users. However, supporting video streaming over the wireless networks is not an easy task due to the dynamic radio propagation environment, limited radio resources as well as Quality of Service (QoS) requirements of the video streaming that need to be satisfied at acceptable levels. Most studies proposed to support video streaming are computationally expensive to be used in Orthogonal Frequency Division Multiple Access (OFDMA) based wireless IP networks. This paper evaluates video streaming performance under three well-known algorithms that are more practical to be used in the OFDMA based wireless IP networks due to their reduced complexity. It is demonstrated via computer simulation that Proportional Fair (PF) algorithm outperforms other well-known algorithms by providing video streaming QoS at acceptable levels whilst maximizing cell throughput.